Hydrogen flux measurements with permeation probes in spherical tokamak QUEST. (July 2016) - Kuzmin, A.; Zushi, H.; Takagi, I.; Sharma, S.K.; Hirooka, Y.; Kobayashi, M.; Sakamoto, M.; Hanada, K.; Onchi, T.; Oyama, Y.; Youshida, N.; Nakamura, K.; et al.
Abstract: Poloidal and radial distributions of the hydrogen flux, both atomic and ion, to the plasma facing materials (PFMs) are measured with four fixed and one movable PdCu membrane probes in the QUEST spherical tokamak. Direct information about hydrogen retention in the areas far from main plasma-wall interaction is essential because the significant part of the global retention is due to atomic hydrogen. Incident hydrogen flux Γ inc is numerically reconstructed by fitting the experimentally measured hydrogen flux Γ p, permeated through the membrane. The sensitivity of the probe is improved when compared with other work which allows dynamic changes of the retention flux to be monitored, allowing detection of 10% of the Γ inc modulation, or ∼10 17  H m −2 s −1 .